PECULIARITIES OF ULTRASTRUCTURAL ORGANISATION OF SPINAL NODES IN ONE-SIDED INJURY OF SCIATIC NERVE AND HYPOTHYROIDISM - Чайковський, Ю.Б.; Raskaley, T.Ya.; Stechenko, L.O.; Raskaley, V.B.; Chuchray, S.M. (World of Medicine and Biology, 2014)
This study deals with the ultrastructural changes in lambar spinal nodes in 6 weeks after injury of schiatic nerve in hypothyroidism. It was established that after sciatic nerve injury in conditions of hypothyroidism after 6 weeks in the lumbar spinal nodes side damaged nerve degenerative changes occurred. In some perikaryons of psevdounipolyar neurons revealed indistinct structural changes that can attest to the beginning of the pathological processes. In the cytoplasm of neurons observed psevdounipolyarnyh other offensive full flowering of irreversible changes due to the presence of significant pathological reactions.
Keywords: hypothyroidism; degeneration; perikaryon; electron microscopy